Effects of cell seeding density on real-time monitoring of anti-proliferative effects of transient gene silencing. Issue 1 (December 2016) - Selli, Cigdem; Erac, Yasemin; Tosun, Metiner
Abstract Background Real-time cellular analysis systems enable impedance-based label-free and dynamic monitoring of various cellular events such as proliferation. In this study, we describe the effects of initial cell seeding density on the anti-proliferative effects of transient gene silencing monitored via real-time cellular analysis. We monitored the real-time changes in proliferation of Huh7 hepatocellular carcinoma and A7r5 vascular smooth muscle cells with different initial seeding densities following transient receptor potential canonical 1 (TRPC1) silencing using xCELLigence system. Huh7 and A7r5 cells were seeded on E-plate 96 at 10, 000, 5000, 1250 and 5000, 2500 cells well−1, respectively, following silencing vector transfection. The inhibitory effects of transient silencing on cell proliferation monitored every 30 min for 72 h. Results TRPC1 silencing did not inhibit the proliferation rates of Huh7 cells at 10, 000 cells well−1 seeding density. However, a significant anti-proliferative effect was observed at 1250 cells well−1 density at each time point throughout 72 h. Furthermore, significant inhibitory effects on A7r5 proliferation were observed at both 5000 and 2500 cells well−1 for 72 h. Conclusions Data suggest that the effects of transient silencing on cell proliferation differ depending on the initial cell seeding density. While high seeding densities mask the significant changes in proliferation, the inhibitory effects of silencing become apparent at lower seeding densities as the entry into log phase is delayed. Using the optimal initial seeding density is crucial when studying the effects of transient gene silencing. In addition, the results suggest that TRPC1 may contribute to proliferation and phenotypic switching of vascular smooth muscle cells.